Cybersecurity of the municipal infrastructure (Law and Safety, 2023)
A modern city is a complex system that requires a unified systematic approach to ensuring public safety, law and order and environmental safety in the face of high levels of both man-made and natural risks. Due to the growing role of information technology in the functioning of a modern city, the threat of cyberattacks on critical municipal infrastructure has increased. The cost of such cyber-attacks can be very high, both for individual victims and for society as a whole. Cyberattacks can lead to the theft of sensitive information, data destruction or the disclosure of personal data. In addition, such attacks can lead to loss of working time and suspension of systems, which can have serious consequences for the city’s viability.The experience of other countries in protecting critical municipal infrastructure from cyber threats has been studied, analysed and summarised. The impact of the latest information technologies (such as the Internet of Things, artificial intelligence, blockchain) on the development of municipal infrastructure, the use of these technologies to protect critical infrastructure from cyberattacks, their advantages and disadvantages compared to classical security technologies have been considered. Particular attention has been paid to the problems of safe automation of modern city management processes such as automation of traffic control systems, environmental monitoring systems, financial systems, power grids, water and gas supply systems, communication systems, and control systems for wastewater treatment plants. The features of cyber attacks and the use of methods for protecting critical infrastructure in the context of hybrid warfare have been examined. Recommendations for a comprehensive increase in the level of protection of municipal critical infrastructure from cyber threats have been provided, taking into account the latest global trends in cybersecurity.
Keywords: cybersecurity; critical municipal infrastructure; Internet of Things (IoT); artificial intelligence; blockchain.